The Organization of the Work in the School and the Students' Participation - Teise de Oliveira Guaranha Garcia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
This article intends to present some reflections on the importance of the students' participation in the organization of the work in the school. It is a presupposition that the implementation of the democratic administration in the public school necessarily demand to consider the part that the students occupy in the process of organization of the pedagogic work. The text, based in obtained results from a research accomplished at a school of the from São Paulo state net that assists to the elementary school teaching (final series) and high school teaching, it examines the theme of the participation in the administration of the public school; the user-students' participation in the organization of the pedagogic work and the results of professionals' actions with views to the democratization of the school administration, especially concerning to the execution of the access and permanence right in the school. It argues, finally, about the importance of the implementation of solid politics that contribute to the democratization of the school practices.